(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the phenology, production and productivity of five strawberry genotypes. for the experiment, the organic production system was used, in the soil under cover of low tunnels. Four Italian selections and one North American cultivar were used. Flowering, fruiting and harvesting and duration of different phenological stages, thermal demand and productive aspects of genotypes were evaluated. The Italian selection CREA FRF LAM01 had the highest production per plant, but all genotypes proved to be suitable for cultivation under the conditions of Laranjeiras do Sul, since they matched the productive reality for the culture in the region.